1996
DOI: 10.1159/000276860
|View full text |Cite
|
Sign up to set email alerts
|

Local Injection Therapy in 107 Patients with Myofascial Pain Syndrome of the Head and Neck

Abstract: Myofascial pain syndrome of the head and neck is a frequent cause of facial pain and is characterized by tender trigger points. In a double-blind study of 107 patients, local injection therapy using one of three solutions was applied at the trigger points by intracutaneous injection of 0.3 ml solution followed by deep infiltration of the site. Results using bupivacaine 0.25%, lignocaine 1% and saline 0.9% were compared. There was no significant difference among groups with respect to reduction of pain and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The most significant limitation of this study is the inability to blind subjects to group allocation as the treatments differ significantly. Additionally, the sample consisted mainly of women and patients below the age of 50, which is inconsistent with published literature 5,10–12 . Consequently, the number of male patients was too small to consider any gender difference.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The most significant limitation of this study is the inability to blind subjects to group allocation as the treatments differ significantly. Additionally, the sample consisted mainly of women and patients below the age of 50, which is inconsistent with published literature 5,10–12 . Consequently, the number of male patients was too small to consider any gender difference.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, the sample consisted mainly of women and patients below the age of 50, which is inconsistent with published literature. 5,[10][11][12] Consequently, the number of male patients was too small to consider any gender difference. The duration and intensity of pain were also similar to those reported in other studies on chronic myofascial pain syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…6). Although local anaesthetics should induce a nerve conduction block that facilitates muscular activity, in one study they were not found to be superior to normal saline 96 . More recently, lidocaine 0.5% injection has been considered as the treatment of choice in MPS 50 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies suggest that TPI with NS solution has similar effects to those seen using TPI with active drugs (31,32). Various substances have been used for TPI.…”
Section: Tpi Agentsmentioning
confidence: 90%
“…In comparing the effectiveness of different therapeutic agents commonly used for TPI, it appears that relief of pain is mainly due to the needle effect rather than to which specific injected medications are used (31)(32)(33)(34)(35)(36)(37)(38). In a doubleblinded study of 107 patients who had pain in the lateral aspect of the face and TPs in the masticatory muscles, local injection therapy using one of three solutions (1 mL 0.25% bupivacaine, 1% lidocaine, or 0.9% saline) yielded no significant differences between the agents in pain relief achieved or in the overall assessment of the therapeutic effect (31). Similarly, in a prospective, randomized evaluation of TPI therapy for lower back pain, there was no significant difference in outcome between injections of lidocaine, lidocaine combined with a steroid, or dry needling at 2 weeks after treatment (37).…”
Section: Tpi Agentsmentioning
confidence: 99%